Adipocytes initiate an adipose-cerebral-peripheral sympathetic reflex to induce insulin resistance during high-fat feeding. (10th September 2019) - Cao, Wei; Shi, Meng; Wu, Liling; Li, Jiaxin; Yang, Zhichen; Liu, Youhua; Wilcox, Christopher S.; Hou, Fan Fan
Abstract : The underlying mechanism by which amassing of white adipose tissue in obesity regulates sympathetic nerve system (SNS) drive to the tissues responsible for glucose disposal, and causes insulin resistance (IR), remains unknown. We tested the hypothesis that high-fat (HF) feeding increases afferent impulses from white adipose tissue that reflexively elevate efferent nerve activity to skeletal muscle (SM) and adipose tissue to impair their local glucose uptake. We also investigated how salt-intake can enhance IR. HF-fed rats received a normal salt (0.4%) or high salt (4%) diet for 3 weeks. High-salt intake in HF fed rats decreased insulin-stimulated 2-deoxyglucose uptake by over 30% in white adipose tissue and SM, exacerbated inflammation, and impaired their insulin signaling and glucose transporter 4 (Glut4) trafficking. Dietary salt in HF fed rats also increased the activity of the adipose-cerebral-muscle renin–angiotensin system (RAS) axes, SNS, and reactive oxygen species (ROS). Insulin sensitivity was reduced by 32% in HF rats during high-salt intake, but was improved by over 62% by interruption of central RAS and SNS drive, and by over 45% by denervation or deafferentation of epididymal fat (all P <0.05). Our study suggest that a HF diet engages a sympathetic reflex from the white adipose tissue that activates adipose-cerebral-muscle RAS/ROS axes and coordinates a reduction in peripheral glucose uptake. These are all enhanced by salt-loading. These findings provide new insight into the role of a reflex initiated in adipose tissue in the regulation of glucose homeostasis during HF feeding that could lead to new therapeutic approaches to IR.